Analisis Asesmen dan Intervensi dalam Proses Menghafalkan Al-Quran: Studi Kasus di Pondok Pesantren An-Nur Yogyakarta - Febiola Cindi Fatika Dita; Nurjannah Nurjannah (IIQ An Nur Yogyakarta, 2023)
Teachers of course have a role in helping their students succeed, as well as in the process of memorizing the Al-Qur'an. In this case, assessment and intervention support teachers' efforts to maximize their role. The aim of this research is to determine the obstacles students face in memorizing the Al-Qur'an, and then determine appropriate interventions and programs according to their needs. This research method is qualitative, using observation in-depth interviews and a case study approach. The results of this research show that the obstacles for santri in memorizing the Koran are the lack of ability of santri to memorize the Al-Qur'an, the lack of enthusiasm of santri in memorizing the Al-Qur'an, and the lack of consistency of santri in memorizing the Al-Qur'an. Then the intervention carried out was to adjust the condition of the students, push and pull and be firm.